Improving outcomes of childhood and young adult non-Hodgkin lymphoma: 25 years of research and collaboration within the framework of the European Intergroup for Childhood Non-Hodgkin Lymphoma. Issue 3 (March 2023) - Beishuizen, Auke; Mellgren, Karin; Andrés, Mara; Auperin, Anne; Bacon, Chris M; Bomken, Simon; Burke, G A Amos; Burkhardt, Birgit; Brugieres, Laurence; Chiang, Alan K S; Damm-Welk, Christine; d'Amore, Emanuele; et al.
Summary: The European Intergroup for Childhood Non-Hodgkin Lymphoma (EICNHL) was established 25 years ago with the goal to facilitate clinical trials and research collaborations in the field both within Europe and worldwide. Since its inception, much progress has been made whereby major improvements in outcomes have been achieved. In this Review, we describe the different diagnostic entities of non-Hodgkin lymphoma in children and young adults describing key features of each entity and outlining clinical achievements made in the context of the EICNHL framework. Furthermore, we provide an overview of advances in biopathology with an emphasis on the role of biological studies and how they have shaped available treatments. Finally, for each entity, we describe future goals, upcoming clinical trials, and highlight areas of research that require our focus going forward.